1,5-Hydride-Shift-Triggered Cyclization for the Synthesis of Unsymmetric Julolidines - Shirokova, Vasilissa V.; Ikonnikova, Viktoria A.; Solyev, Pavel N.; Lushpa, Vladislav A.; Korlyukov, Alexander A.; Volodin, Alexander D.; Baleeva, Nadezhda S.; Baranov, Mikhail S.; Mikhaylov, Andrey A. (Synthesis, 2021)
Directly accessible 8-substituted tetrahydroquinolines undergo 1,5-hydride-shift-triggered cyclization to provide difficult to access julolidine derivatives in yields of 21–98% under scandium(III) triflate catalysis. Additionally, the scope of the reaction, several follow-up transformations and a remarkable side process discovered during optimization of the conditions are highlighted.
Keywords: julolidine; 1,5-hydride shift; redox-neutral reaction; tetrahydroquinoline; catalysis